PENGARUH MUSIK INSTRUMENTAL TERHADAP KENYAMANAN PADA PASIEN GAGAL GINJAL KRONIK YANG MENJALANI HEMODIALISIS DI RSUP DR. SARDJITO - , IKA INDAR WATI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Background:Hemodialysis is one therapy for chronic renal failure. During hemodialysis, patients report a discomfort, because impact from the dialysis. Dialysis cause an inconvenience of a client (Caminha, 2009). Nurse canprovide an activities that can entertain or distract the patient, one of them are using music. Objective:The purpose of this study was to determine the effect of instrumental music on comfort in hemodialysis patientin RSUP dr. Sardjito. Methods:A Quasi- Experimental was utilized, there are 50 people divided into 27 people in experimental group and 23 people in control group. Treatment was given four time, twice a week during Januari until Februari 2014 in hemodialysis unit RSUP dr. Sardjito.Data were gathered using short-GCQ (General Comfort Questionnaire).Man-Whitney was used to analyse the data. Results: Comfort levels measured in 1st and 2nd meeting are not affected by instrumental music, with p value respectively 0,135 (p>0,05) and 0,092 (p>0,05), however the study show a significant value of comfort levels in 3rd and 4th meeting, wtih p value respectively 0,04(p<0,05) and 0,008 (p<0,05). Conclusion: This study demonstrate that instrumental music significantly affects on patients comfort during 3rd and 4th meeting. Key Words: music, hemodialysis, comfort